Problems of Management of Migration Processes in Contemporary Russia - V. A. Volokh (Управление)
The article analyzes the migration situation in Russia and the relevant results in accordance with the Concept of state migration policy of the Russian Federation for the period till 2025. Successful work of the Federal Migration Service is shown. However, Presidential Decree No. 156 of 5 April 2016 “On the improvement of public administration in the sphere of control over the circulation of narcotic drugs, psychotropic substances and their precursors and in the sphere of migration” the Federal Migration Service was abolished, and its functions were fully transferred to the Ministry of Internal Affairs of Russia. The author notes that for an absolute community of experts and specialists in the field of population migration, this decision was an unexpected. The author analyzes the situation of institution support for the state migration policy and prospects for further development. Particular attention is paid to the process of establishing institutional support for the state migration policy of Russia.